2012
DOI: 10.1523/jneurosci.5826-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Frontostriatal Interaction Aligns with Reduced Primary Reward Processing under Serotonergic Drugs

Abstract: Recently, functional interactions between anteroventral prefrontal cortex and nucleus accumbens (NAcc) have been shown to relate to behavior counteracting reward-desiring (Diekhof and Gruber, 2010). Downregulation of the reward system by serotonin has also been suggested as the mode of action accounting for unsatisfactory effects of serotonin reuptake inhibitors (SSRIs) such as insufficient alleviation or even increase of anhedonia, and loss of interest. However, understanding of the in vivo mechanisms of SSRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 31 publications
2
34
0
2
Order By: Relevance
“…Indeed, a recent pharamacologic study found that the antidepressant efficacy of SSRIs modulated the FC between ventral striatum and anteroventral prefrontal cortex, which is associated with the reward system (36). Networks related to depressive behavior may coexist in different loops between striatum and prefrontal areas, and thus the superiority illusion in particular might be best viewed as the products of larger-scale interactions of different loops and different molecular systems.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent pharamacologic study found that the antidepressant efficacy of SSRIs modulated the FC between ventral striatum and anteroventral prefrontal cortex, which is associated with the reward system (36). Networks related to depressive behavior may coexist in different loops between striatum and prefrontal areas, and thus the superiority illusion in particular might be best viewed as the products of larger-scale interactions of different loops and different molecular systems.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, depressed undergraduates who were not taking antidepressant medication completed a probabilistic selection task. Recent functional neuroimaging studies have shown that antidepressant medication affects areas of the brain reward system such as the striatum (Abler, Gron, Hartmann, Metzger, & Walter, 2012;McCabe & Mishor, 2011;Ossewaarde et al, 2011). In one study, antidepressant medication led to increased activation of the brain reward system of previously unmedicated MDD patients, such that there were no significant differences between medicated MDD patients and healthy controls (Stoy et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Though the amygdala has primarily been linked to an array of processes related to negative emotions, such as conditioning and memory of fear (Kim et al, 2013), fMRI studies have challenged this notion by showing amygdala and OFC reactivity in response to appetitive stimuli, possibly reflecting these regions' role in reward and motivation related behavioral processes (Gottfried et al, 2003). In fact, serotonin also seems to play a central role in these processes, as previously highlighted by Kranz et al (Kranz et al, 2010) and empirically supported by recent studies on SSRI-related sexual dysfunction (Abler et al, 2011) and biased reward processing (Abler et al, 2012). Investigations into anatomical and functional networks integrating the OFC and the amygdala describe both direct, from limbic and sensory regions, and indirect information flow to the amygdala via the OFC.…”
Section: Influence Of Ssris On Effective Connectivitymentioning
confidence: 95%